Sex Differences in Long-Term Mortality and Functional Outcome After Rehabilitation in Patients With Severe Stroke - Scrutinio, Domenico; Battista, Petronilla; Guida, Pietro; Lanzillo, Bernardo; Tortelli, Rosanna (Frontiers in Neurology, 2020)
Objective. We sought to determine sex differences in outcomes in patients with severe stroke who had been admitted to inpatient rehabilitation. Methods. We studied 1,316 patients aged 18 to 99 (mean 72) classified as case-mix groups 0108, 0109, and 0110 of the Medicare case-mix classification system. These groups encompass the most severe strokes. Three outcomes were analyzed: 1) three-year mortality from admission to rehabilitation; 2) combined outcome of transfer to acute care or death within 90 days from admission to rehabilitation; 3) functional outcome, including proportional recovery in motor functioning and good functional outcome as defined by achievement of a Functional Independence Measure (FIM)-motor score ≥65 points at discharge. Multivariable regression analyses were used to assess sex-difference in each outcome between women and men. The covariates examined included age, marital status, comorbidities, time from stroke onset to rehabilitation admission <30 days, ischemic stroke, dysphagia, neglect, motor FIM score at admission, and cognitive FIM score at admission. Results. Kaplan-Meier estimated 3-year mortality rate was 20.7% in women and 22.0% in men. The crude hazard ratio (HR) of death for women compared with men was 0.94 (95% CI 0.74-1.20). After adjustment for significant covariates, the HR of 3-year mortality was 0.73 (95% CIs 0.56-0.96; p=.025). Comorbidity, including diabetes, anemia, coronary artery disease, atrial fibrillation, and chronic obstructive pulmonary disease, significantly increased mortality risk by 49% to 88%. The incidence of the combined outcome was 8.3% in women and 8.4% in men. The crude HR of the combined end-point for women compared with men was 1.05 (95% CI 0.72-1.53). After adjustment for significant covariates, the HR was 0.95 (95% CIs 0.65-1.40; p=.810). Likewise, no significant difference in proportional recovery or in the rate of achievement of a good functional outcome between women and men was observed. Conclusion. Among patients admitted to inpatient rehabilitation after severe stroke, women and men had comparable crude mortality rates at 3 years. After multivariable adjustment, however, women had lower mortality risk. No sex-differences in the risk of being transferred to acute care or dying within 90 days from admission to rehabilitation or in responsiveness to rehabilitation were observed.